A Gut Analysis Technique for Pinpointing Egg-Specific Predation Events. Issue 3 (7th June 2019) - Hagler, James R; Mostafa, Ayman M
Abstract: A universal food immunomarking technique (UFIT) is described for postmortem gut analysis detection of predation on the egg stage of Lygus hesperus Knight (Hemiptera: Miridae). Collops vittatus Say (Coleoptera: Melyridae) and Hippodamia convergens Guérin-Méneville (Coleoptera: Coccinellidae) were fed a single L. hesperus egg that was marked with rabbit and chicken sera proteins. The protein-marked egg remnants were detectable in the guts of the majority of the predators by each sera-specific enzyme-linked immunosorbent assay (ELISA) for 3 to 6 h after a feeding event. A novel technique was then developed to expose protein-marked eggs to predators that simulated the L. hesperus endophytic oviposition behavior. The procedure entailed embedding L. hesperus eggs in an artificial substrate that mimicked the stem of a plant. A predator feeding choice study was then conducted in cages that contained a cotton plant and artificial stems containing endophytic (concealed) and exophytic (exposed) egg patches. The endophytic and exophytic egg treatments were marked with chicken and rabbit protein, respectively. The gut analyses revealed that higher proportions of both predator populations contained remnants of the exophytic egg treatment and L. hesperus eggs were more vulnerable to C. vittatus than H. convergens . This study shows how the UFIT can be used to pinpoint stage-specific feeding activity on two distinct egg exposure treatments (endophytic and exophytic) of the same species.